Management of School Operational Assistance Funds (Policy Implementation Study of the Minister of Education and Culture Regulation) - Anggita Nirmalasari; Praptining Sukowati; Dodot Sapto Adi (ABM: International Journal of Administration, Business and Management, 2025)
This study aims to describe and analyze the implementation of the School Operational Assistance Fund management policy and identify the supporting and inhibiting factors. The research was conducted at Public Elementary School 1 Brotonegaran, Ponorogo Regency. The data analysis technique used a qualitative method with a descriptive approach. The findings in the study show that implementing the BOS Fund management policy at Public Elementary School 1 Brotonegaran has been running quite well, although it still faces various challenges. Analysis based on the Edward III theory revealed that communication between school principals and the management team was quite evident through training and technical guidelines. However, socialization to student guardians is still not optimal. Regarding resources, limited funds, and untimely disbursements are the main obstacles. School principals, BOS treasurers, and operators' commitment to managing the funds was relatively high, but coordination with external parties was less effective. In addition, the bureaucracy in the verification and validation process of the funds often delayed the disbursement, which impacted the smooth implementation of school programs. The results of this study will contribute to providing recommendations for increasing the transparency of communication with student guardians, optimizing the budget, improving the disbursement of funds, training managers, and periodic monitoring and evaluation for the effectiveness of BOS fund management.